Phytoplankton compositions in Alaaras torist Island Lake – Iraq (Baghdad Science Journal, 2013)
The study includes the phytoplankton compositions in Alaaras Lake , in summer 2008 and winter , spring , summer 2009. Samples were collected from three selected sites at north , middle and south of lake. A total of 74 taxa of phytoplankton were identified . The diatoms were the dominated by 44 taxa represented 82.8% of the total indentified species, followed by green algae ( Chlorophyta ) of 20 taxa (8.5%), and blue green algae (Cyanophyta of 7 taxa (7.2%). Tow species were recorded of Pyrrophyta and one species of Euglenophyta .The seasonal variation for Diatoms density showed tow peaks during Autumn and summer. Few species were dominated during the most studied period such as Cocconeis placentula var. euglypta, Synedra fasciculata and Cymbell affinis .